2015
DOI: 10.1007/s00018-015-1891-5
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular EP2 prostanoid receptor promotes cancer-related phenotypes in PC3 cells

Abstract: Prostaglandin E2 (PGE2) and hypoxia-inducible factor-1α (HIF-1α) affect many mechanisms that have been involved in the pathogenesis of prostate cancer (PC). HIF-1α, which is up-regulated by PGE2 in LNCaP cells and PC3 cells, has been shown to contribute to metastasis and chemo-resistance of castrate-resistant PC (a lethal form of PC) and to promote in PC cells migration, invasion, angiogenesis and chemoresistance. The selective blockade of PGE2-EP2 signaling pathway in PC3 cells results in inhibition of cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 59 publications
0
32
0
Order By: Relevance
“…Hif1a was 1.83-fold upregulated in the knockout mice, even when the tumors were small. A previous study reported that HIF-1α is upregulated by PGE 2 , contributing to metastasis and chemoresistance, as well as the promotion of prostate cancer cell migration, invasion and angiogenesis (31). Mmps degrade extracellular matrix and facilitate the migration of tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…Hif1a was 1.83-fold upregulated in the knockout mice, even when the tumors were small. A previous study reported that HIF-1α is upregulated by PGE 2 , contributing to metastasis and chemoresistance, as well as the promotion of prostate cancer cell migration, invasion and angiogenesis (31). Mmps degrade extracellular matrix and facilitate the migration of tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of PGE 2 on non‐transformed prostate epithelial cells are currently unknown, despite they may be relevant in non‐malignant proliferative diseases of the prostate associated with chronic inflammation of the prostate such are BPH or proliferative inflammatory atrophy (Bardan, Dumache, Dema, Cumpanas, & Bucuras, ; Thapa & Ghosh, ). Here we found in immortalized, non‐malignant prostate epithelial RWPE‐1 cells that PGE 2 , again through the axis iPGE 2 ‐iEP receptors‐EGFR‐HIF‐1α, inhibits cell adhesion and stimulates cell proliferation, migration and in vitro angiogenesis (i.e., the same effects than in PC3 cells (Fernández‐Martínez & Lucio‐Cazaña, ; Madrigal‐Martínez et al, )). Since iPGE 2 mediates the growth‐stimulating effects of PGE 2 on prostate epithelial cells, regardless they are benign or malign ones, the pharmacological inhibition of PGT could be a novel therapeutic approach to treat prostate proliferative diseases associated with chronic inflammation.…”
Section: Introductionmentioning
confidence: 79%
“…It is generally accepted that the biological actions of PGE 2 are mediated by plasma membrane G protein‐coupled EP receptors which are located at the cell membrane. However, we have found that PGE 2 has to reach the intracellular compartment and activate a subset of EP receptors, which is located intracellularly, as a prerequisite for being effective in PC3 cells (Fernández‐Martínez & Lucio‐Cazaña, ; Madrigal‐Martínez et al, ). This is a non‐canonical intracrine mechanism of PGE 2 action for which the energetically active influx of PGE 2 (accounting for almost 100% of PGE 2 internalization), is mediated by the prostaglandin transporter (PGT), a member of the organic anion transporter family (Nomura, Lu, Pucci, & Schuster, ; Schuster, ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations